Comparison among three polymerase chain reaction assays on detection of DNA from Leishmania in biological samples from patients with american cutaneous leishmaniasis - João Guilherme Lino da Silva; Thiago Miranda da Silva; Eduardo de Figueiredo Peloso; George Luiz Lins Machado-Coelho; Wilson Mayrink; Marília Caixeta Franco Ariosa; Paulo Márcio de Faria e Silva; Marcos José Marques (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: The study analyzed positivity of polymerase chain reaction (PCR) on detection of DNA from Leishmania in patients' samples. METHODS: Extracted DNA was submitted to L150/L152, 13Y/13Z, and seminested PCR (snPCR). RESULTS: Results were evidenced by bands of approximately 120, 720, and 670 bp for L150/L152, 13Y/13Z, and snPCR, respectively. L150/L152, 13Y/13Z, and snPCR positivity indexes were 76.9, 56.4, and 9.2 (p>0.05), respectively, for suspected and 93.7, 68.7, and 84.4 (p<0.05), respectively, for confirmed. CONCLUSIONS: Preliminary results showed that these assays, mainly L150/L152 and snPCR, can detect Leishmania DNA and carry potential on laboratory diagnosis of leishmaniasis.